Rational constructive solution of protective structures of covering trusses under dynamic loads - BILYK, Artem; TERNOVIY, Maksym (Ways to Improve Construction Efficiency, 2024)
The article presents the results of studies on the search for rational parameters of protective structures of small-span roof trusses under dynamic loads. The main properties of such structures, the requirements they must meet, and the adopted provisions are considered. The main principles of designing protective structures of steel structure roofs are formulated to ensure the required strength and stability of the structure under impulse loads. The aim of the work is to develop a methodology for alternative design to determine the rational (limitedly optimal) height of a steel truss roof with a cross lattice under short-term impulse loads. For the selected type of structure with known general parameters of the structure, the main technical solutions are adopted in alternative design. According to the refined classification, the technical and economic criteria for comparing alternatives are described by various functions: static, dynamic, convex non-convex, polymodal, nonlinear, discrete, discontinuous, undifferentiated and partially separable. The search for a global optimum of such target functions for a generalized problem of optimal design of a spatial structural system using existing analytical methods has certain difficulties. This is due to the fact that various design solutions with different topology, different calculation schemes and a discrete set of geometric characteristics of element sections cannot be reduced to the description of a single system of functional dependencies, since private criteria of parameters of individual equations depend on different variables. It is known that in a weakly structured problem, parametric dependencies between ascending and variable parameters are described not only by explicit analytical expressions, but also by discrete mathematics methods based on predicate calculation, and the functions of private comparison criteria are algorithmic. For the variant design and determination of the rational height of the steel truss, a beam analogy is used. As a calculation scheme, a calculation scheme of an ideal I-beam is adopted taking into account the shear deformation of the cross section. Shear deformations of the section take into account the increase in deflections of the beam-rod steel truss relative to the I-beam. The target function of steel consumption is recorded depending on the height and purlin of the steel roof truss, the dynamic factor is also taken into account. Analytical dependencies for determining the height of trusses are obtained, taking into account their dynamic characteristics with additional load from the action of a blast wave at the end of the roof block. The target criterion is the mass of structures, which allows us to move on to cost indicators.